2019
DOI: 10.3389/fgene.2019.01162
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of 10-Year Data Assessed the Diagnostic Accuracy and Efficacy of Cytogenomic Abnormalities in Current Prenatal and Pediatric Settings

Abstract: Background: Array comparative genomic hybridization (aCGH), karyotyping and fluorescence in situ hybridization (FISH) analyses have been used in a clinical cytogenetic laboratory. A systematic analysis on diagnostic findings of cytogenomic abnormalities in current prenatal and pediatric settings provides approaches for future improvement.Methods: A retrospective analysis was performed on abnormal findings by aCGH, karyotyping, and FISH from 3,608 prenatal cases and 4,509 pediatric cases during 2008–2017. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…The detection rate of abnormalities by SNP-array was 12.3%, including 4.1% of cases with numerical chromosome anomalies, 0.4% with LOH and 7.8% with CNV ( Table 2 and Figure 1A ). And the detection rate of clinically significant CNVs (i.e., CNVs classified as P or LP) by SNP-array was 2.6% ( Table 2 ), which is similar to a previous systematic review that overall 295/12362 (2.4%) have CNVs with associated clinical significance ( Callaway et al, 2013 ) and a recent retrospective analysis of 10-year data reported that the abnormality detection rate of pathogenic CNVs by aCGH is 2.59% for prenatal cases ( Chai et al, 2019 ). Moreover, the 5000 samples were categorized into five groups according to the indications for invasive prenatal testing: anomaly on ultrasonography, advanced maternal age, abnormal result on maternal serum screening, abnormal NIPT results and other indications.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The detection rate of abnormalities by SNP-array was 12.3%, including 4.1% of cases with numerical chromosome anomalies, 0.4% with LOH and 7.8% with CNV ( Table 2 and Figure 1A ). And the detection rate of clinically significant CNVs (i.e., CNVs classified as P or LP) by SNP-array was 2.6% ( Table 2 ), which is similar to a previous systematic review that overall 295/12362 (2.4%) have CNVs with associated clinical significance ( Callaway et al, 2013 ) and a recent retrospective analysis of 10-year data reported that the abnormality detection rate of pathogenic CNVs by aCGH is 2.59% for prenatal cases ( Chai et al, 2019 ). Moreover, the 5000 samples were categorized into five groups according to the indications for invasive prenatal testing: anomaly on ultrasonography, advanced maternal age, abnormal result on maternal serum screening, abnormal NIPT results and other indications.…”
Section: Discussionsupporting
confidence: 86%
“…that the abnormality detection rate of pathogenic CNVs by aCGH is 2.59% for prenatal cases (Chai et al, 2019). Moreover, the 5000 samples were categorized into five groups according to the indications for invasive prenatal testing: anomaly on ultrasonography, advanced maternal age, abnormal result on maternal serum screening, abnormal NIPT results and other indications.…”
Section: Discussionmentioning
confidence: 99%
“…aCGH analysis has been used extensively for prenatal and postnatal detection of constitutional copy number variants and showed significantly improved diagnostic efficacy and accuracy [ 19 ]. However, the application of aCGH to detect somatic CNAs in various cancers has been adapted slowly due to the difficulty in dissecting the clonal heterogeneity from CNAs and the deficiency of supporting databases to interpret abnormal findings [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found out the higher rate of prenatal diagnosis, the change of indications prior to NIPT, the declining trend of termination rate as well as PPV for each SCA by NIPT, However, the limitation of this study is that can not follow-up all false-positive cases, the existence of CPM can not be ruled out. Most of SCA cases can not be diagnosed until childbearing age, and some of them can not be diagnosed throughout lifetimes [32]. Therefore, the sensitivity, false-positive rate and falsenegative rate of NIPT screening for SCA can not be accurately calculated.…”
Section: Discussionmentioning
confidence: 99%